2018
DOI: 10.22226/2410-3535-2018-3-252-257
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures upon explosion welding and processes which prevent joining of materials

Abstract: The present paper examines features of interface structure and analyzes possible risk zones for two to a certain degree alternative objects manufactured from composites produced by explosive welding. One of those is a chemical reactor vessel; the other is a petrochemical reactor vessel (a coke drum). The engineering of a chemical reactor vessel is an example of a successful implementation of explosive welding. The analysis of the chemical reactor wall structure containing a coppertantalum welded joint revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Then, under the action of the shock wave, the molten copper and steel mixed together and flowed with the wave crest, and finally converge to the vortex region where the pressure in front of the wave is lowest [1,16,19]. Greenberg et al [22,23] found the same phenomenon in aluminiumtantalum and copper-titanium explosive welding interfaces, vortex zones are formed near the cusps and valleys. Due to the low impact energy, we did not find a similar vortex zone at the lower-interface, as shown in Figure 3c.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Then, under the action of the shock wave, the molten copper and steel mixed together and flowed with the wave crest, and finally converge to the vortex region where the pressure in front of the wave is lowest [1,16,19]. Greenberg et al [22,23] found the same phenomenon in aluminiumtantalum and copper-titanium explosive welding interfaces, vortex zones are formed near the cusps and valleys. Due to the low impact energy, we did not find a similar vortex zone at the lower-interface, as shown in Figure 3c.…”
Section: Resultsmentioning
confidence: 89%
“…As a resu a number of the most severely deformed copper microstructures melted in the first plac and more liquid copper was mixed with the soften or even molten iron, which can evidenced by the fact that copper occupies more volume fraction in the vortex regio Then, under the action of the shock wave, the molten copper and steel mixed together an flowed with the wave crest, and finally converge to the vortex region where the pressu in front of the wave is lowest [1,16,19]. Greenberg et al [22,23] found the same phenom non in aluminium-tantalum and copper-titanium explosive welding interfaces, vort zones are formed near the cusps and valleys. Due to the low impact energy, we did n find a similar vortex zone at the lower-interface, as shown in Figure 3c.…”
Section: Resultsmentioning
confidence: 99%